PENGARUH CUSTOMER SATISFACTION TERHADAP CUSTOMER LOYALITY, SWITCHING COST SEBAGAI VARIABEL MEDIASI - Mohammad Dzulkifli (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The objectives of the study are to reveal the influence of customer satisfaction on customer loyalty based on users of mobile data services PT. Indosat Ooredoo Tbk, switching cost as a mediating variable. The data was obtained by involving 189 respondents and using the Structural Equation Model (SEM) with AMOS 2.4. The results show that customer satisfaction affects customer loyalty, and switching cost mediates the relationship between customer satisfaction and customer loyalty. It implies that the company has to pay attention to customer satisfaction, customer loyalty, and switching costs at the mobile data service, in a service provider. This finding provides insights into the importance of improving customer satisfaction, and switching costs in increasing customer loyalty of the company.